Sulfur and Ti3+ co-Doping of TiO2 Nanotubes Enhance Photocatalytic H2 Evolution Without the Use of Any co-catalyst - Ji, Lei; Zhou, Xuemei; Schmuki, Patrik (Chemistry - An Asian Journal, 2019)
TiO2 nanotubes were successfully co-doped with sulfur and Ti3+ states using a facile annealing treatment in H2/H2S gas mixture. The obtained nanotubes were investigated for their photocatalytic performance and characterized by SEM, XRD, XPS, EPR, IPCE, IMPS and Mott-Schottky measurements. The synthesized co-doped TiO2 nanotubes show an enhanced photocatalytic hydrogen production rate compared to tubes that were treated only in pure H2 or H2S atmosphere—this without the presence of any co-catalyst. It was found that sulfur in co-doped TiO2 exists in the form of S2− and a small quantity of S4+/S6+, which leads to a narrowing of the band gap. However, the enhanced absorption of light in the visible range is not the key reason for the improved photocatalytic performance. We ascribe the enhanced photocatalytic activity to a synergetic effect of S mid-gap states and disordered Ti3+ defects that facilitate photo generated electron transfer.
CRIS-Team Scopus Importer:2019-07-19
Keywords: hydrogen evolution; nanotubes; oxygen vacancy; sulfur doping; titanium